Monitoring and environmental impact of Ferrol Bay pollution - Guillén, Oscar (1998)
Ferrol Bay is considered one of the most polluted areas of the Peruvian coast, mainly due to the residues of the industrial fishing and iron and steel industry. Added to this are domestic waste, oil spills caused during loading and unloading operations and the activities of the port, causing a deterioration of recreational beaches, affecting fishing resources and human health. Anoxic conditions were observed in the bay of Ferrol in the spring of 1994 and the summer of 1966, with an average dissolved oxygen of 0.20 and 0.18 ml / l, respectively. The most contaminated area is the one located near the liquid effluent discharges of Petro Perú - Pesca Perú, with values ​​greater than 250 mg / l of DB05, 0.00 ml / l of dissolved oxygen, temperature of 18.00 ° C and very low chlorophyll "a" values, in the winter of 1998. The El Niño phenomenon 1997-98 had great negative effects on the marine ecosystem, producing changes in it and the fisheries, resulting in low productivity, instability of the fishing industry and a negative socio-economic impact for the country. Oceanographic conditions after the El Niño event 1997-98, showed that they were normalizing, an increase in the average dissolved oxygen content was also observed (3.64 ml / 1), suggesting a partial decontamination of the waters.